Application Of Project Management Principles In The Public Sector's Architectural Design Practice - Sandanasamy, Reymund (2002)
The implementation of MS-ISO 9000 Standards in Public Works Department of Malaysia, had an impact on the future direction of the project management phenomenon in the architectural design practice. It is through this implementation exercise that the public sector's architectural design practice made its first attempt to understand the concept of project management and its philosophy. The MS-ISO 9000 Standards which incorporates project management practice in its guidelines are the main source of direction and guiding principles for PWD' s architectural design practice. Hence this saw the need for project management thinking in the public sector. The main thrust of this study is to investigate and ascertain through questionnaire survey, the adoptability and relevancy of project management principles in the public sector's architectural design practice. A total of 90 survey returns were received , which represented 81 .8 percent of the total 110 questionnaire forms distributed . The sample population for the study is focused on the managerial and professional level of the public sector's architectural design practice. The data gathered through various survey instruments were subjected to rigorous statistical analysis with the use of Statistical Package for Social Science, version 10.5 ( 1999) using descriptive and correlation statistical analysis. It was found that majority of the architects recognize the characteristics of project management and its relevancy in their creative orientated practice. Thus , it is evident in the survey findings that project management principles as defined in this thesis is applicable in the public sector's architectural design practice, and generally has increased the awareness of the architects towards time, cost and quality requirements of the projects. The elements of system approach namely project organization mission, project objectives, project goals and short-term targets are found in the PWD' s architectural design practice. All these elements contribute to the functioning of the architectural design practice. It is therefore apparent from the survey that project management principles, after its inception, contributes to the overall success of the PWD' s building projects. However the thesis has also identified several drawbacks of the project management principles in the architectural design practice, but they do not adversely affect the contribution of the project management practice in the continuous success of the PWD 's architectural practice.